Carnivalesque humour in the 2017 women’s March protest posters against trumpism : a multimodal discourse analysis - Sami Alhasnawi,; Raja’a Mizhir Radhi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The 2017 Women's March is a histo-political icon in the US for women's rights, voice, solidarity, collective identity and power to resist Trump’s ideologized masculinity, racism and social hegemony. Although the multitude of protest posters in the Women’s March has become the core of research from different perspectives, there is still a scarce attention given to how Trump’s body compared to Putin’s was used to ridicule Trumpism through protestors’ multimodal protest posters. To cover such a research gap, this work, in turn, focuses mainly on grotesque imagery in the 2017 Women’s March for protesters to delegitimize and scorn Trump’s political agenda for ‘America First’ and ‘Make America Great Again’. Based on Bakhtin’s (1984a) carnival theory and carnivalesque as an overarching theoretical framework and Kress and van Leeuwen’s (2006) visual social semiotics as a methodological approach to the selected protest posters corpus, we found that a multimodal grotesque imagery of the Trump-Putin’s relationship was manipulated in the 2017 Women’s March as a counter discourse to vent protesters’ anger and resistance against Trumpism. A work like this will significantly add more to sociolinguistics and political linguistics in terms of considering linguistic and nonlinguistic units in communication. As such, this implies broadening the toolkit of analysis in applied linguistics.